The Islamic Character Education at Darussalam Gontor Boarding School and its Implications for Students' Discipline - Muhammad Wahyudi; Mochammad Fachturrahman Spama Putra; Muh. Rifki; Muhammad Slamet Riyadi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Islamic character education shapes students' behavior, particularly in boarding schools like Pondok Modern Darussalam Gontor. Gontor is well-known for blending religious teachings with general education, aiming to develop students’ characters in line with Islamic values, which underpins its disciplinary practices. However, despite its structured approach, Gontor faces challenges in ensuring that Islamic values taught in class are consistently practiced in everyday life. This study zeroes in on Gontor's educational system, assessing how effectively its character education fosters discipline and handles current challenges. It sheds light on Gontor's comprehensive approach and offers practical recommendations for other pesantren to strengthen their character education systems, ensuring they remain relevant and effective in today's evolving world.